A disseminação do modelo da casa quadripartida na cidade industrial. O caso do Porto no primeiro terço do século XX
This dissertation focuses on the analysis of the quadruple house as an affordable housing model forthe industrial city. Its genesis is directly linked to a new set of demands instigated by the IndustrialRevolution. The changes in the social organization and in the economic and labour dynamics since thesecond half of the 18th century had great effects in the cities through the creation of new urban centersand above all by its unprecedented growth. The housing crisis which resulted can be summed up by ahigh and fast demand and the consequent deterioration of living conditions affecting most of the workingclass. Given the signs of threat by the city's environment to the public health, the reform movement of the19th century was based mainly on the rise of hygienism which addressed important transformations to thehousing architecture and to the urban management, marking the normalization of decent housing as wellas setting a precedent for issues to be further developed by modernism. Under the reform, the quadruplehouse model was inserted in the ideological wing promoting individual and detached housing and itssystematization in the city of Mulhouse, France, was the subject of a wide dissemination. Inseparableto the industrial logic, the reproducibility of the carré mulhousien as an economic and healthy housingsolution for the working class was a phenomenon to be observed in very different geographies, includingthe city of Porto. Since the model's importation in 1899, in a specific urban context, other cases of itsapplication were to follow during the first third of the twentieth century, only to confirm the existence ofcertain special features that enrich the scrutiny of the architectural model's use, likewise an underlyingregulatory nature to the relationship between the investor and the inhabitant. By using the quadruplehousing design, Frank Lloyd Wright shows an application of that model outside the scope of the worker'sdwelling, proposing it as a modernist housing solution, more precisely during the 1930's and early 1940's.Thus, invented in an experimental context and based essentially on a simple geometric formula, thishousing model evolved and adapted in multiple levels (spatial, technical, urban, ideological, etc.), on aninternational scale and for nearly one and a half centuries.